Discovery of hyperstable carbohydrate‐active enzymes through metagenomics of extreme environments. (21st October 2019) - Strazzulli, Andrea; Cobucci‐Ponzano, Beatrice; Iacono, Roberta; Giglio, Rosa; Maurelli, Luisa; Curci, Nicola; Schiano‐di‐Cola, Corinna; Santangelo, Annalisa; Contursi, Patrizia; Lombard, Vincent; Henrissat, Bernard; Lauro, Federico M.; et al.
Abstract : The enzymes from hyperthermophilic microorganisms populating volcanic sites represent interesting cases of protein adaptation and biotransformations under conditions where conventional enzymes quickly denature. The difficulties in cultivating extremophiles severely limit access to this class of biocatalysts. To circumvent this problem, we embarked on the exploration of the biodiversity of the solfatara Pisciarelli, Agnano (Naples, Italy), to discover hyperthermophilic carbohydrate‐active enzymes ( CAZymes ) and to characterize the entire set of such enzymes in this environment ( CAZome ). Here, we report the results of the metagenomic analysis of two mud/water pools that greatly differ in both temperature and pH ( T  = 85 °C and pH 5.5; T  = 92 °C and pH 1.5, for Pool1 and Pool2, respectively). DNA deep sequencing and following in silico analysis led to 14 934 and 17 652 complete ORFs in Pool1 and Pool2, respectively. They exclusively belonged to archaeal cells and viruses with great genera variance within the phylum Crenarchaeota, which reflected the difference in temperature and pH of the two Pools. Surprisingly, 30% and 62% of all of the reads obtained from Pool1 and 2, respectively, had no match in nucleotide databanks. Genes associated with carbohydrate metabolism were 15% and 16% of the total in the two Pools, with 278 and 308 putative CAZymes in Pool1 and 2, corresponding to ~ 2.0% of all ORFs. Biochemical characterization of two CAZymes of a previously unknown archaeon revealed a novel subfamily GH5_19 β‐mannanase/β‐1, 3‐glucanase whose hemicellulose specificity correlates with the vegetation surrounding the sampling site, and a novel NAD + ‐dependent GH109 with a previously unreported β‐ N ‐acetylglucosaminide/β‐glucoside specificity. Databases: The sequencing reads are available in the NCBI Sequence Read Archive (SRA) database under the accession numbers SRR7545549 (Pool1) and SRR7545550 (Pool2). The sequences of GH5_Pool2 and GH109_Pool2 are available in GenBank database under the accession numbers MK869723 and MK86972, respectively. The environmental data relative to Pool1 and Pool2 (NCBI BioProject PRJNA481947) are available in the Biosamples database under the accession numbers SAMN09692669 (Pool1) and SAMN09692670 (Pool2). Abstract : The metagenomic investigation of the solfatara Pisciarelli (Naples) reported here revealed a rich CAZome, the collection of the environmental carbohydrate‐active enzymes (CAZy), offering the opportunity to discover novel CAZy with new biochemical property. Our study represents the first CAZome study of a hydrothermal vent revealing CAZyme families previously unknown in Archaea, putative enzymes with promising potential for utilization in next‐generation biorefineries, and novel glycoside hydrolases with interesting substrate specificities and stability.